1968
DOI: 10.1577/1548-8659(1968)97[380:eomsia]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Main Stem Impoundments and Channelization upon the Limnology of the Missouri River, Nebraska

Abstract: Rigid control has been imposed upon the Missouri River by impounding over one-half of the upper 1500 miles and by channeling most of the remaining river within permanent, narrow banks. These controls have caused environmental changes in the lower Missouri River, as shown by this study, of adjacent unchannelized and channelized sections of river below the main stem impoundments. Impoundments have regulated flow by evening maximum and minimum discharges and improved downstream water quality by decreasing turbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Further, studies have shown that Missouri River reaches with braided river channels and a diversity of aquatic habitats within the floodplain have diverse fish communities (Schmulbach et al, 1975;Kallemeyn and Novotny, 1977;Jacobson et al, 2001) and are superior for sport fish production as compared to channelized and/or modified reaches (Groen and Schmulbach, 1978). Such reaches also support more diverse invertebrate communities (Morris et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have shown that Missouri River reaches with braided river channels and a diversity of aquatic habitats within the floodplain have diverse fish communities (Schmulbach et al, 1975;Kallemeyn and Novotny, 1977;Jacobson et al, 2001) and are superior for sport fish production as compared to channelized and/or modified reaches (Groen and Schmulbach, 1978). Such reaches also support more diverse invertebrate communities (Morris et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…After channelization, however, the Missouri River below Sioux City, Iowa, was changed into a fairly narrow and swift flowing river, resulting in a shortening of the channel by 125 km and reduction of the wetted area by nearly 64% (Whitley and Campbell, 1974). Likewise, the construction of six major reservoirs in the middle reaches of the river has changed water quality above and below the dams (Morris et al, 1968) and altered the hydrology of the river (Hesse and Mestl, 1993). These major alterations have essentially divided the Missouri River into three zones, an upper zone upstream from the major alterations, a middle zone with short free-flowing reaches between reservoirs, and a zone downstream of the impoundments which is entirely channelized except for the reach between Yankton, South Dakota and Sioux City, Iowa (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Six mainstem dams were also constructed between 1937 and 1963, primarily to control flooding and to provide adequate depth for navigation on the lower river (Galat et al, 1996). The associated reservoirs cover nearly half of the upper 2,500 km of the Missouri River (Morris et al, 1968). The result of these alterations has been a metamorphosis from a once natural, complex floodplain river to a relatively artificial, simple system (Whitley and Campbell, 1974), with division of the river into three management zones: an upper, relatively unaltered (or least altered) zone upstream from the reservoirs, a zone between the reservoirs where short stretches of unchannelized river remain, and a lower channelized zone (Fig.…”
Section: Study Areamentioning
confidence: 99%